Electrode plate, battery and electric equipment

By using conductive fiber materials in the electrode material film layer of lithium battery to form a conductive network, the problem of insufficient rate performance of lithium battery is solved, and lower internal resistance and better rate performance are achieved.

CN119852302APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311348820.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing lithium batteries have shortcomings in rate performance, resulting in poor battery performance during high rate charging and discharging.

Method used

By using conductive fiber material as the conductive agent in the electrode material film layer, the conductive fiber material includes organic fibers and a conductive layer coated on the surface of the organic fibers, forming a good conductive network, thereby reducing the resistance of the electrode sheet.

Benefits of technology

It effectively reduces the internal resistance of the battery, reduces the polarization of the battery during charging and discharging, and significantly improves the battery's rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852302A_ABST
    Figure CN119852302A_ABST
Patent Text Reader

Abstract

The invention provides an electrode plate, a battery and electric equipment, the electrode plate comprises an electrode material film layer, the electrode material film layer comprises a conductive fiber material, the conductive fiber material comprises an organic fiber and a conductive layer wrapping at least part of the surface of the organic fiber, and the conductive layer comprises a conductive material. By adding the conductive fiber material as the conductive agent into the electrode material film layer, the conductive fiber material has good conductivity and good dispersibility, and can form a good conductive network in the electrode material film layer, so that the resistance of the electrode plate can be effectively reduced, and a battery with low internal resistance is obtained; polarization of the battery in the charging and discharging process is reduced, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to an electrode plate, a battery and an electrical device. Background Art

[0002] Battery cells represented by lithium-ion batteries have the advantages of reliable working performance, no pollution, and no memory effect, so they are widely used. For example, as environmental protection issues are increasingly valued and new energy vehicles become more and more popular, the demand for power battery cells will show explosive growth. As the scope of battery applications becomes wider and wider, higher requirements are placed on the rate performance of batteries, so it is necessary to improve the rate performance of batteries. Summary of the invention

[0003] The present application provides an electrode plate, a battery and an electrical device, wherein the electrode plate can improve the rate performance of the battery.

[0004] In a first aspect, the present application provides an electrode plate, comprising an electrode material film layer, wherein the electrode material film layer comprises a conductive fiber material, wherein the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a portion of the surface of the organic fibers, wherein the conductive layer comprises a conductive material.

[0005] According to the present application, by adding a conductive fiber material as a conductive agent in the electrode material film layer, the conductive fiber material has good conductivity and good dispersibility, and can form a good conductive network in the electrode material film layer, thereby effectively reducing the resistance of the electrode plate, and then obtaining a battery with lower internal resistance, reducing the polarization of the battery during the charge and discharge process, and improving the battery rate performance.

[0006] In some embodiments, the aspect ratio of the conductive fiber material is 200 to 1500. Preferably, the aspect ratio is 400 to 800. In this case, the conductive fiber material is more likely to form a conductive network in the electrode material film layer, the resistance of the electrode plate is lower, the internal resistance of the obtained battery is smaller, and the rate performance is better.

[0007] In some embodiments, the average diameter of the conductive fiber material is 10-100 nm. In this case, the battery has a better rate performance while taking into account the energy density of the battery. Preferably, the average diameter is 20-60 nm.

[0008] In some embodiments, the average length of the conductive fiber material is 2 to 50 μm. In this case, the conductive network in the electrode material film layer is better, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. Preferably, the average length is 10 to 30 μm.

[0009] In some embodiments, the thickness of the conductive layer is 3 to 20 nm. In this case, the conductive fiber material has better conductivity, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. Preferably, the thickness of the conductive layer is 5 to 10 nm.

[0010] In some embodiments, the organic fiber includes at least one of protein fiber, polysaccharide fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber or polyether fiber. The above organic fiber has good flexibility, and thus the conductive fiber material has better flexibility, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, and the rate performance is better; and the above organic fiber has a lower density, which can improve the energy density of the battery.

[0011] In some embodiments, the conductive material includes at least one of a metal element, an alloy, or a conductive metal oxide. In this case, the conductive fiber material has better conductivity, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better.

[0012] In some embodiments, the metal element includes at least one of copper, nickel, aluminum, silver or titanium; and / or the alloy includes at least one of copper alloy, nickel alloy, aluminum alloy, silver alloy or titanium alloy; and / or the conductive carbon includes at least one of carbon nanotubes, conductive carbon black or graphene; and / or the conductive metal oxide includes at least one of zinc oxide, indium tin oxide or tin oxide; and / or the conductive polymer includes at least one of polypyrrole, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid).

[0013] In some embodiments, the mass percentage of the conductive fiber material in the electrode material film layer is 0.01% to 3%.

[0014] The second aspect of the present application provides a method for preparing an electrode sheet, comprising the following steps:

[0015] Dispersing a conductive fiber material, an active material and a binder in a solvent to obtain an electrode slurry, wherein the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a portion of the surface of the organic fibers;

[0016] The electrode slurry is dried to form an electrode material film layer.

[0017] According to the present application, since the conductive fiber material has good dispersibility, the conductive fiber material can be directly dispersed in a solvent to obtain an electrode slurry, which is then coated and dried to form an electrode material film layer, and a good conductive network is formed in the electrode material film layer, thereby reducing production costs.

[0018] In some embodiments, the step of dispersing the conductive fiber material, the active material and the binder in a solvent to obtain the electrode slurry specifically includes: first dispersing the conductive fiber material in a solvent to obtain a conductive fiber material dispersion, and then dispersing the conductive fiber material dispersion, the active material and the binder in the solvent to obtain the electrode slurry. In this case, the conductive fiber material has better dispersibility in the electrode slurry, is easier to form a conductive network, the resistance of the electrode sheet is smaller, and the rate performance is better.

[0019] A third aspect of the present application provides a battery, comprising the electrode plate described in any embodiment of the first aspect or the electrode plate prepared by the method described in any embodiment of the second aspect.

[0020] According to the present application, the battery includes the electrode plate described in any embodiment of the first aspect or the electrode plate prepared according to the method described in any embodiment of the second aspect, and thus has the beneficial effects of the first aspect or the second aspect.

[0021] A fourth aspect of the present application provides an electrical device, comprising the battery described in any embodiment of the third aspect.

[0022] The present application provides an electrode plate, and by using a conductive fiber material with good dispersibility as a conductive agent in the electrode material film layer, the internal resistance of the battery can be effectively reduced, thereby reducing the polarization of the battery during the charge and discharge process and improving the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope (SEM) image of the conductive fiber material in one embodiment of the present application.

[0024] Figure 2 It is a SEM image of the surface of the electrode material film layer in the electrode plate in one embodiment of the present application.

[0025] Figure 3 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0026] Figure 4 yes Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0027] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.

[0028] Figure 6 is a schematic diagram of a battery according to one embodiment of the present application.

[0029] Figure 7 yes Figure 6 An exploded view of a battery according to an embodiment of the present application is shown.

[0030] Figure 8 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.

[0031] Description of reference numerals:

[0032] 1 battery; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0033] Below, the embodiments of the electrode plates, batteries and electrical equipment of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0034] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0035] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0037] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0038] As described in the background technology above, with the widespread application of batteries, higher requirements are placed on the rate performance of batteries. Batteries generally include positive electrode sheets, negative electrode sheets and separators, wherein the resistance of the positive electrode sheets and the negative electrode sheets will affect the internal resistance of the battery, increase the polarization of the battery during the discharge process, and thus have a certain impact on the rate performance of the battery.

[0039] Currently, the main method to reduce the internal resistance of electrode plates is to add a certain amount of conductive agent. Commonly used conductive agents include conductive graphite, carbon nanotubes and other materials. Although conductive graphite is low in price, it mainly transmits electrons in the form of point contact in the electrode material film layer, so the effect of reducing the resistance of the electrode plate is relatively poor. Although carbon nanotubes mainly transmit electrons in the form of line contact in the electrode material film layer, the problem is that the dispersion of carbon nanotubes is poor, and it is difficult to form a conductive network in the electrode material film layer. Therefore, its effect in reducing the resistance of the electrode plate is limited, and the effect of improving the battery rate performance is limited.

[0040] In view of this, the present application provides an electrode plate, wherein the electrode material film layer of the electrode plate uses a conductive fiber material as a conductive agent, and the conductive fiber material has good dispersibility and can form a good conductive network in the electrode material film layer, thereby effectively reducing the resistance of the electrode plate, thereby reducing the internal resistance of the battery, reducing the polarization of the battery during the charge and discharge process, and improving the rate performance of the battery. The electrode plate, battery, and electrical equipment provided by the present application are described in detail below.

[0041] Electrode

[0042] In a first aspect, the present application provides an electrode plate, comprising an electrode material film layer, the electrode material film layer comprises a conductive fiber material, the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a portion of the surface of the organic fibers, the conductive layer comprises a conductive material.

[0043] According to the present application, the electrode plate uses a conductive fiber material as a conductive agent, wherein the conductive fiber material includes organic fibers and a conductive layer at least partially coated on the surface of the organic fibers. It can be understood that organic fiber refers to a fiber material formed by an organic polymer. Organic fibers generally have more functional groups (for example, polysaccharide fibers contain a large number of hydroxyl groups, protein fibers contain more amino and carboxyl groups, polyester fibers contain more ester groups, etc.). Organic fibers are mainly aggregated through the interaction forces of surface functional groups (such as hydrogen bonds, etc.). These interaction forces are weaker than the intermolecular forces between carbon nanotube fibers and are more easily destroyed under appropriate conditions (such as adding dispersants, ultrasound, etc.). Therefore, organic fibers have better dispersibility; on the other hand, since organic polymers are composed of many repeating organic molecular units, these organic molecular units are connected by covalent bonds to form a long chain structure, which can slide and stretch freely to a certain extent under the action of external stress, so organic fibers have better flexibility; and generally speaking, organic fibers have poor conductivity. Conductive fiber materials are obtained by coating organic fibers with good dispersibility and flexibility with a conductive layer, so that the conductive fiber materials have better conductivity while inheriting the good dispersibility and flexibility of organic fibers. Based on this, when the conductive fiber material is used to prepare the electrode plate, due to its good dispersibility and flexibility, the conductive fiber material is easier to disperse and entangle on the surface of the active material, thereby forming a good conductive network in the electrode material film layer, which can effectively reduce the contact resistance between the active materials and between the active materials and the current collector, reduce the resistance of the electrode plate, and then reduce the internal resistance of the battery, thereby reducing the polarization of the battery during charging and discharging, and reducing the voltage drop of the battery during high-rate charging and discharging, thereby improving the rate performance of the battery.

[0044] Figure 1 The SEM image of the conductive fiber material in one embodiment of the present application is shown. The conductive fiber material can exist in the form of a single fiber, is easy to disperse, and is not easy to agglomerate. Figure 2 A SEM image of the surface of the electrode material film layer in the electrode plate in one embodiment of the present application is shown. The conductive fiber material can be dispersed on the surface of other components in the electrode material film layer to form a conductive network to reduce the resistance of the electrode plate.

[0045] It is worth mentioning that since the density of organic fibers is relatively low, using this conductive fiber material as a conductive agent is also beneficial to improving the energy density of the battery.

[0046] It should be noted that the organic fiber in the conductive fiber material has a well-known meaning in the art, and refers to a fiber material formed by a polymer, which can be determined by known instruments and methods. For example, for the coniferous wood fiber, polyester fiber, and silk protein fiber used in some embodiments of the present application, the following method can be used for determination: an ion milling instrument is used to perform ion polishing treatment on the cross section of the electrode sample containing such conductive fiber material, and an EDS spectrometer is used to perform local element analysis on the cross section of the organic fiber in the conductive fiber, and twenty fiber samples are randomly selected for testing, and whether it is the above-mentioned organic fiber is determined based on the C, O or N element content in the test results (the C element content is generally 10wt% to 90wt%).

[0047] In some embodiments, the conductive fiber material has an aspect ratio of 200-1500.

[0048] In some of the above embodiments, the aspect ratio of the conductive fiber material is further limited, and the aspect ratio has a certain influence on the flexibility of the conductive fiber material, and the flexibility of the conductive fiber material will affect the formation of the conductive network in the electrode material film layer. When the aspect ratio of the conductive fiber material is 200 to 1500, the conductive fiber material has better dispersibility and flexibility, and the conductive fiber material is easier to form a conductive network in the electrode material film layer, thereby more effectively reducing the resistance of the electrode plate, the internal resistance of the battery is lower, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. For example, the aspect ratio of the conductive fiber material can be 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, or any range thereof. Preferably, the aspect ratio of the conductive fiber material can be 400-800.

[0049] In some embodiments, the conductive fiber material has an average diameter of 10 to 100 nm.

[0050] In some of the above embodiments, the average diameter of the conductive fiber material is further limited. It is understandable that when the content of the conductive fiber material in the electrode material film layer is constant, the diameter of the conductive fiber material will affect the formation of the conductive network. When the average diameter of the conductive fiber material is 10 to 100 nm, less conductive fiber material can form a good conductive network in the electrode material film layer, which is beneficial to improve the energy density of the battery. For example, the average diameter of the conductive fiber material can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, or within the range of any of the above values. Preferably, the average diameter is 20 to 60nm.

[0051] In some embodiments, the conductive fiber material has an average length of 2 to 50 μm.

[0052] In some of the above embodiments, the average length of the conductive fiber material is further limited. It is understandable that the length of the conductive fiber material will affect the formation of the conductive network. Generally speaking, the longer the length, the longer the conductive network, and the better the effect of reducing the resistance of the electrode sheet. However, the length will also affect the dispersion of the conductive fiber material. When the average length of the conductive fiber material is 2 to 50 μm, the conductive network in the electrode material film layer is better, the resistance of the electrode sheet is lower, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. Preferably, the average length is 10 to 30 μm.

[0053] In some embodiments, the conductive layer has a thickness of 3 to 20 nm.

[0054] In some of the above embodiments, the thickness of the conductive layer is further defined. The thickness of the conductive layer will affect the conductivity of the conductive fiber material. Generally speaking, the thickness of the conductive layer is positively correlated with the conductivity of the conductive fiber material. In addition, the thickness of the conductive layer will also affect the flexibility of the conductive fiber material, and thus have a certain influence on the resistance of the electrode plate. When the thickness of the conductive layer is 3 to 20 nm, the conductive fiber material has better conductivity, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. For example, the thickness of the conductive layer can be 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or within the range of any of the above values. Preferably, the thickness of the conductive layer is 5 to 10 nm.

[0055] The aspect ratio, average diameter, average length, and thickness of the conductive layer of the conductive fiber material are all within the known range in the art and can be tested using methods or instruments known in the art. For example, a scanning electron microscope is used to randomly select twenty fiber samples of the conductive fiber material in the pole piece for testing, and the average length and average diameter are measured and calculated, and then the aspect ratio is calculated according to aspect ratio = average length / average diameter. An ion mill is used to perform ion polishing on the cross section of the pole piece sample, and then a scanning electron microscope is used to randomly select twenty fiber samples of the conductive fiber material in the pole piece for testing, and the average thickness of the conductive layer is measured and calculated.

[0056] In some embodiments, the organic fiber includes at least one of a protein fiber, a polysaccharide fiber, a polyester fiber, a polyamide fiber, or a polyether fiber.

[0057] In some of the above embodiments, the type of organic fiber is further limited. The above organic fiber has good flexibility, and thus the conductive fiber material has better flexibility, so that it is easier to form a good conductive network in the electrode plate, the resistance of the electrode plate is lower, and the internal resistance of the battery is smaller; and the above organic fiber has a low density, which can improve the energy density of the battery.

[0058] It should also be noted that the types of organic fibers mentioned above are only exemplary, and those skilled in the art can select organic fibers with good flexibility according to actual needs.

[0059] In some embodiments, the organic fiber includes at least one of polysaccharide fiber, polyester fiber and polyamide fiber. The above organic fibers have better thermal stability, are more conducive to processing and utilization, and reduce production costs.

[0060] In some embodiments, the sources of organic fibers include but are not limited to artificial synthesis or natural acquisition. For example, the protein fiber can be silk protein fiber, and the polysaccharide fiber can be cotton fiber, hemp fiber, flax fiber, kapok fiber, grass fiber, coniferous wood fiber, etc.

[0061] In some embodiments, the conductive material may include at least one of conductive carbon, metal element, alloy, conductive metal oxide or conductive polymer. It is understood that the conductive layer provides conductivity for the conductive fiber material, and the conductive layer can be formed by coating organic fibers with conductive materials known in the art to obtain the conductive fiber material.

[0062] The preparation method of the conductive fiber material includes but is not limited to coating the organic fiber surface with a corresponding conductive layer by chemical plating, vacuum plating, magnetron sputtering, vapor deposition, in-situ polymerization, solution impregnation, etc. It can also be prepared by methods known in the art.

[0063] In some embodiments, the conductive material may include a conductive polymer. Conductive polymers generally have a smaller Young's modulus than other conductive materials, which can make the conductive fiber material more flexible, thereby facilitating the formation of a conductive network.

[0064] In some embodiments, the conductive polymer may include, but is not limited to, polypyrrole and PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid)). As an example, a conductive fiber material whose conductive layer is polypyrrole or PEDOT:PSS is prepared by an in-situ polymerization process, which specifically includes: preselecting an organic fiber material with a suitable average length, average diameter and aspect ratio, immersing the organic fiber material in a corresponding monomer solution, performing in-situ polymerization under suitable conditions, controlling the thickness of the conductive layer by controlling the monomer concentration and polymerization time, and obtaining a conductive fiber material with a desired average length, average diameter and aspect ratio after washing and drying.

[0065] In some embodiments, when the conductive material is polypyrrole and the thickness of the conductive layer is 3 to 20 nm, the mass percentage of the conductive material in the conductive fiber material can be 10% to 30%. At this time, the conductive layer covers the organic fiber more uniformly and densely, and the conductive fiber material has better conductive properties.

[0066] In some embodiments, the conductive material may include at least one of a metal element, an alloy, or a conductive metal oxide.

[0067] In some of the above-mentioned embodiments, the type of conductive layer is further limited. Since metal elements, alloys, and conductive metal oxides have higher conductivity and better conductivity than conductive carbon and conductive polymers, in addition, the conductive fiber material has better dispersibility and is easier to form a conductive network in the electrode material film layer. Therefore, the conductive fiber material has better conductivity, the resistance of the electrode plate is lower, the internal resistance of the battery is smaller, the polarization of the battery is smaller during the charge and discharge process, and the rate performance is better.

[0068] It is worth mentioning that although metal elements, alloys and conductive metal oxides have high electrical conductivity, they are generally not used as conductive agents for electrode plates. The main reason is that it is costly to prepare the above materials into a morphology suitable for conductive agents (such as fibrous or granular), and the density is large, which is not conducive to controlling costs and reducing the energy density of the battery. In addition, even if the above materials are prepared into fibers, it is difficult to form a good conductive network due to their poor flexibility. Therefore, in some embodiments, the conductive fiber material obtained by coating the above materials on the surface of organic fibers can overcome the above problems through organic fibers while utilizing its high electrical conductivity, thereby effectively reducing the resistance of the electrode plates and thus reducing the internal resistance of the battery.

[0069] In some embodiments, the metal element may include, but is not limited to, copper, nickel, aluminum, silver, titanium and other materials. As an example, when the conductive material is copper or nickel, the conductive fiber material can be prepared by a chemical plating process, specifically including: pre-selecting an organic fiber material with a suitable average length, average diameter and aspect ratio, then subjecting the organic fiber material to surface treatment, water washing, pre-preg, activation, water washing, degumming and other process treatments, and finally performing a chemical plating process, controlling the thickness of the conductive layer by controlling the process temperature and time, and obtaining the conductive fiber material with the desired average length, average diameter and aspect ratio after water washing and drying. As another example, when the conductive material is aluminum, the conductive fiber material can be prepared by an atomic deposition process, specifically including: pre-selecting an organic fiber material with an average length, average diameter and a suitable aspect ratio, and then controlling the thickness of the conductive layer by controlling the atomic deposition time to obtain the conductive fiber material with the desired average length, average diameter and aspect ratio.

[0070] In some embodiments, when the conductive material is copper or nickel and the thickness of the conductive layer is 3 to 20 nm, the mass percentage of the conductive material in the conductive fiber material can be 90% to 99%. At this time, the conductive layer covers the organic fiber more uniformly and densely, and the conductive fiber material has better conductive properties.

[0071] In some embodiments, when the conductive material is aluminum and the thickness of the conductive layer is 3 to 20 nm, the mass percentage of the conductive material in the conductive fiber material can be 25% to 50%. At this time, the conductive layer covers the organic fiber more uniformly and densely, and the conductive fiber material has better conductive properties.

[0072] In some embodiments, the alloy may include at least one of a copper alloy, a nickel alloy, an aluminum alloy, a silver alloy, or a titanium alloy. As an example, when the conductive material is a copper alloy or a nickel alloy, the conductive fiber material may be prepared by a chemical plating process.

[0073] In some embodiments, the conductive metal oxide may include but is not limited to zinc oxide, indium tin oxide, tin oxide, etc. As an example, when the conductive material is tin oxide, the conductive fiber material can be obtained by the following method: preselecting an organic fiber material with a suitable average length, average diameter and aspect ratio, then subjecting the organic fiber material to surface treatment, water washing, pre-impregnation, activation, water washing, degumming and other process processes, and finally performing a chemical plating process, controlling the thickness of the conductive layer by controlling the process temperature and time, and obtaining the conductive fiber material with the desired average length, average diameter and aspect ratio after water washing and drying.

[0074] In some embodiments, when the conductive material is tin oxide and the thickness of the conductive layer is 3 to 20 nm, the mass percentage of the conductive material in the conductive fiber material can be 75% to 90%. At this time, the conductive layer covers the organic fiber more uniformly and densely, and the conductive fiber material has better conductive properties.

[0075] In some embodiments, the conductive carbon may include at least one of carbon nanotubes, conductive carbon black or graphene. As an example, when the conductive material is carbon nanotubes, the conductive fiber material may be obtained by a solution impregnation method, specifically comprising: preselecting an organic fiber material with a suitable average length, average diameter and aspect ratio, impregnating the organic fiber material in a single-walled carbon nanotube dispersion, standing for a period of time, controlling the thickness of the conductive layer by controlling the average diameter of the single-walled carbon nanotubes, the concentration of the single-walled carbon nanotube dispersion and the impregnation time, and obtaining the conductive fiber material with the desired average length, average diameter and aspect ratio after washing and drying.

[0076] In some embodiments, when the conductive material is conductive carbon and the thickness of the conductive layer is 3 to 20 nm, the mass percentage of the conductive material in the conductive fiber material can be 10% to 30%. At this time, the conductive layer covers the organic fiber more uniformly and densely, and the conductive fiber material has better conductive properties.

[0077] When it is necessary to explain, the mass percentage of the conductive material in the conductive fiber material can be measured by known methods and instruments. For example, the mass of the organic fiber without the conductive layer is weighed as m1, the mass of the conductive fiber material after the conductive layer is weighed as m2, and the mass percentage of the conductive material in the conductive fiber material is (m2-m1) / m2×100%.

[0078] In some embodiments, the mass percentage of the conductive fiber material in the electrode material film layer is 0.01% to 3%.

[0079] In some of the above embodiments, the mass percentage of the conductive fiber material in the electrode material film layer is further limited. At this time, the conductive fiber material can form a better conductive network in the electrode material film layer, so that the resistance of the electrode plate is smaller, the internal resistance of the battery is smaller, the polarization of the battery during charging and discharging is smaller, and the rate performance is better. For example, the mass percentage of the conductive fiber material in the electrode material film layer can be 0.01%, 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, 0.5%, 0.8%, 1%, 2%, 3%, or within the range composed of any of the above values. Preferably, the mass percentage of the conductive fiber material in the electrode material film layer is 0.05% to 1%.

[0080] It should also be noted that the conductive fiber material is used as a conductive agent in the electrode material film layer, and its content in the electrode material film layer can be selected according to the content of conductive agents in the electrode material film layer known in the art. The limitation of its mass percentage in the above embodiment is only a further preference.

[0081] In some embodiments, the electrode plate includes a current collector, and the electrode material film layer is disposed on at least one surface of the current collector.

[0082] As an example, the current collector has two surfaces opposite to each other in its own thickness direction, and the electrode material film layer is disposed on any one or both of the two opposite surfaces of the current collector.

[0083] In some embodiments, the current collector may be a metal foil or a composite current collector. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). As an example, the electrode pole piece is a positive pole piece and the current collector is aluminum foil. As another example, the electrode pole piece is a negative pole piece and the current collector is copper foil.

[0084] In some embodiments, the electrode material film layer includes an active material, and the active material may be a positive electrode active material or a negative electrode active material commonly used in the art, and there is no particular limitation on the specific type.

[0085] As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0086] The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0087] In some embodiments, the electrode material film layer further includes a binder, which may be a binder commonly used in the art, and there is no particular limitation on the specific type.

[0088] As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0089] In some embodiments, the electrode material film layer may also optionally include other conductive agents. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0090] In some embodiments, the electrode material film layer may also optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0091] Method for preparing electrode sheet

[0092] The second aspect of the present application provides a method for preparing an electrode sheet, comprising the following steps:

[0093] Dispersing a conductive fiber material, an active material and a binder in a solvent to obtain an electrode slurry, wherein the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a portion of the surface of the organic fibers;

[0094] The electrode slurry is dried to form an electrode material film layer.

[0095] According to the present application, since the conductive fiber material has good dispersibility, the conductive fiber material can be directly dispersed in a solvent to obtain an electrode slurry, which is then coated and dried to form an electrode material film layer, and a good conductive network is formed in the electrode material film layer, thereby reducing production costs.

[0096] In some embodiments, the electrode slurry is coated on a current collector and dried to form an electrode material film layer to obtain an electrode sheet.

[0097] In some embodiments, the conductive fiber material, active material, binder, and current collector can be selected with reference to any embodiment of the first aspect, so as to achieve corresponding beneficial effects.

[0098] In some embodiments, the solvent may include water, dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1-propanol, 2 ... At least one of alcohol, 1,3-butanediol, 1,5-pentanediol, hexylene glycol, glycerol, trimethylolpropane, pentaerythritol, sorbitol, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, acetone, methyl ethyl ketone, methyl propyl ketone, cyclopentanone, ethyl acetate, γ-butyrolactone and ε-propiolactone. As an example, the solvent may be water. As another example, the solvent may be N-methylpyrrolidone.

[0099] In some embodiments, the conductive fiber material is first dispersed in a solvent to obtain a conductive fiber material dispersion, and then the conductive fiber material dispersion, active material and binder are dispersed in a solvent to obtain an electrode slurry. In this case, the conductive fiber material has better dispersibility in the electrode slurry, is easier to form a conductive network, and the resistance of the electrode plate is smaller.

[0100] In some embodiments, the conductive fiber material dispersion also includes a dispersant, which may be a dispersant commonly used in the art, and there is no particular limitation on the specific type. The dispersant may be at least one of sodium dodecyl sulfate (SDS), polyvinyl alcohol, and polyacrylamide. As an example, the dispersant may be polyethylene glycol.

[0101] In some embodiments, after drying to form the electrode material film layer, it may be subjected to steps such as cold pressing to obtain an electrode plate.

[0102] Battery

[0103] A third aspect of the present application provides a battery, comprising an electrode sheet according to any embodiment of the first aspect or an electrode sheet prepared by a method according to any embodiment of the second aspect.

[0104] According to the present application, the battery includes the electrode plate of any embodiment of the first aspect or the electrode plate prepared according to the method of any embodiment of the second aspect, and thus has the beneficial effects of the first aspect or the second aspect.

[0105] In some embodiments, the electrode plate serves as at least one of a positive electrode plate and a negative electrode plate. As an example, the electrode plate serves as a positive electrode plate. As another example, the electrode plate serves as a negative electrode plate. As another example, the electrode plate serves as both a positive electrode plate and a negative electrode plate.

[0106] Typically, the battery also includes a separator and an electrolyte. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode.

[0107] [Electrolytes]

[0108] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0109] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0110] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0111] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0112] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0113] [Isolation film]

[0114] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0115] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0116] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0117] In some embodiments, a battery may include a battery cell including the above-described electrode assembly.

[0118] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0119] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0120] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.

[0121] In some embodiments, reference Figure 4, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0122] In some embodiments, the battery may further include a case; the battery cells are accommodated in the case.

[0123] The battery may include one or more battery cells, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery.

[0124] Furthermore, in the above battery, a plurality of battery cells are assembled to form a battery module. Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0125] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0126] Figure 6 and Figure 7 1 is an example of a battery. Figure 6 and Figure 7 The battery 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0127] In some embodiments, the battery may be a secondary battery.

[0128] Electrical devices

[0129] In a third aspect, the present application further provides an electrical device, comprising a battery according to any embodiment of the third aspect.

[0130] The battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0131] As the power-consuming device, the above-mentioned battery can be selected according to its usage requirements.

[0132] Figure 8 The power consumption device is taken as an example, and the power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0133] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery including only a battery cell may be used as a power source.

[0134] Example

[0135] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0136] Example 1-1

[0137] (1) Preparation of positive electrode sheet

[0138] First, the conductive fiber material is dispersed in N-methylpyrrolidone to obtain a 6wt% conductive fiber material dispersion, and then the conductive fiber material dispersion, lithium iron phosphate and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone, and the mixture is fully stirred and evenly mixed to prepare a positive electrode slurry, wherein the mass ratio of lithium iron phosphate, conductive fiber material and polyvinylidene fluoride is 98.35:0.15:1.5, and the organic fiber in the conductive fiber material is coniferous wood fiber, the conductive layer is nickel (nickel is coated on the surface of the coniferous wood fiber), and the mass percentage of the conductive layer in the conductive fiber material is 90%, the aspect ratio is 200, the average diameter is 30nm, the average length is 6μm, and the thickness of the conductive layer is 5nm. The positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, and then dried, cold pressed and cut to obtain a positive electrode sheet.

[0139] (2) Preparation of negative electrode sheet

[0140] Artificial graphite, conductive fiber material, binder styrene-butadiene rubber and thickener sodium carboxymethyl cellulose (CMC-Na) are dispersed in deionized water, and the mixture is stirred and mixed thoroughly to prepare a negative electrode slurry, wherein the mass ratio of artificial graphite, conductive fiber material, styrene-butadiene rubber and sodium carboxymethyl cellulose is 96.9:0.1:2.0:1.0, and in the conductive fiber material, the organic fiber is coniferous wood fiber, the conductive layer is copper (copper is coated on the surface of the coniferous wood fiber), and the mass percentage of the conductive layer in the conductive fiber material is 95%, the aspect ratio is 500, the average diameter is 40nm, the average length is 20μm, and the thickness of the conductive layer is 5nm. The negative electrode slurry is coated on both sides of the negative electrode current collector copper foil, and then dried, cold pressed and cut to obtain a negative electrode sheet.

[0141] (3) Preparation of electrolyte

[0142] At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 is dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 is 1 mol / L.

[0143] (4) Preparation of isolation membrane

[0144] A commercially available PE polymer microporous film with a thickness of 7 μm was used as the separator of the lithium-ion battery.

[0145] (5) Preparation of lithium-ion batteries

[0146] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in order, and cold-pressed (during which the separator and the electrode sheet are bonded) to obtain a battery cell; the battery cell is placed in an outer package, and the prepared electrolyte is added. After packaging, standing, formation, aging and other processes, a lithium-ion battery is obtained.

[0147] Example 1-2 to Example 1-4

[0148] It is substantially the same as Example 1-1, except that conductive fiber materials with different aspect ratios are obtained by changing the average length of the organic fibers in the conductive fiber material. The specific parameters are shown in Table 1.

[0149] Examples 1-5

[0150] It is roughly the same as Example 1-1, except that different conductive fiber materials are obtained by changing the average length, average diameter and thickness of the conductive layer of the organic fibers in the conductive fiber material. The mass percentage of the conductive layer in the conductive fiber material is 90%. Other specific parameters are shown in Table 1.

[0151] Examples 1-6

[0152] It is roughly the same as Example 1-1, except that different conductive fiber materials are obtained by changing the average length, average diameter and thickness of the conductive layer of the organic fibers in the conductive fiber material. The mass percentage of the conductive layer in the conductive fiber material is 95%. Other specific parameters are shown in Table 1.

[0153] Examples 1-7

[0154] It is roughly the same as Example 1-1, except that different conductive fiber materials are obtained by changing the average length, average diameter and thickness of the conductive layer of the organic fibers in the conductive fiber material. The mass percentage of the conductive layer in the conductive fiber material is 97%. Other specific parameters are shown in Table 1.

[0155] Examples 1-8

[0156] It is roughly the same as Example 1-1, except that different conductive fiber materials are obtained by changing the average length, average diameter and thickness of the conductive layer of the organic fibers in the conductive fiber material. The mass percentage of the conductive layer in the conductive fiber material is 98%. Other specific parameters are shown in Table 1.

[0157] Examples 1-9

[0158] It is roughly the same as Example 1-1, except that different conductive fiber materials are obtained by changing the average length, average diameter and thickness of the conductive layer of the organic fibers in the conductive fiber material. The mass percentage of the conductive layer in the conductive fiber material is 99%. Other specific parameters are shown in Table 1.

[0159] Examples 1-10

[0160] It is substantially the same as Example 1-3, except that different conductive fiber materials are obtained by changing the type of the conductive layer in the conductive fiber material, the conductive layer is aluminum, and the mass percentage of the conductive layer in the conductive fiber material is 32%. Other specific parameters are shown in Table 1.

[0161] Embodiment 1-11

[0162] It is roughly the same as Example 1-3, except that different conductive fiber materials are obtained by changing the type of the conductive layer in the conductive fiber material. The conductive layer is nickel oxide, and the mass percentage of the conductive layer in the conductive fiber material is 85%. Other specific parameters are shown in Table 1.

[0163] Examples 1-12

[0164] It is substantially the same as Example 1-3, except that different conductive fiber materials are obtained by changing the type of the conductive layer in the conductive fiber material, the conductive layer is polypyrrole, and the mass percentage of the conductive layer in the conductive fiber material is 15%. Other specific parameters are shown in Table 1.

[0165] Example 1-13 and Example 1-14

[0166] It is substantially the same as Example 1-3, except that different conductive fiber materials are obtained by changing the type of organic fiber in the conductive fiber material. The specific parameters are shown in Table 1.

[0167] Examples 1-15

[0168] It is roughly the same as Example 1-3, and the only difference is that the preparation method of the positive electrode slurry is: directly disperse lithium iron phosphate, conductive fiber material, and binder polyvinylidene fluoride in N-methylpyrrolidone, and then stir and mix them evenly to prepare a positive electrode slurry, wherein the mass ratio of lithium iron phosphate, conductive fiber material, and polyvinylidene fluoride is 98.35:0.15:1.5.

[0169] Examples 1-16

[0170] It is roughly the same as Example 1-3, except that: first, carbon nanotubes (average diameter of 30nm, average length of 24μm, aspect ratio of 800) are dispersed in N-methylpyrrolidone to obtain a 0.4wt% carbon nanotube dispersion, and then the carbon nanotube dispersion, lithium iron phosphate and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone, and the positive electrode slurry is prepared after sufficient stirring and mixing, wherein the mass ratio of lithium iron phosphate, carbon nanotubes and polyvinylidene fluoride is 98.35:0.15:1.5.

[0171] Examples 1-17

[0172] It is substantially the same as Example 1-3, except that conductive carbon black SP is used in the positive electrode sheet instead of conductive fiber material.

[0173] Comparative Example 1-1

[0174] It is substantially the same as Example 1-16, except that conductive carbon black SP is used in the negative electrode plate instead of conductive fiber material.

[0175] The lithium ion batteries obtained in the above-mentioned Examples 1-1 to 1-17 and Comparative Example 1-1 were subjected to the following tests. The test results are shown in Table 1.

[0176] (1) 4C rate charging window test

[0177] Test environment: protection voltage 2.4V~3.65V;

[0178] Step-1: Capacity test

[0179] 1. Leave the battery at 25°C for 30 minutes;

[0180] 2. 0.33C constant current discharge to 2.5V at 25℃;

[0181] 3. Leave to stand at 25℃ for 30min;

[0182] 4. 0.33C constant current charging to 3.65V at 25℃, constant voltage charging, cut-off current 0.05C;

[0183] 5. Leave to stand at 25℃ for 30min;

[0184] 6. Discharge to 2.5V at 0.33C at 25℃, and calculate the actual capacity of the battery cell to be C0 Ah;

[0185] 7. Leave to stand at 25℃ for 30min;

[0186] Step-2: Continuous 4C rate charging window test

[0187] 1) Stand at 25℃ for 30min;

[0188] 2) 0.33C constant current discharge to 2.5V at 25℃;

[0189] 3) Stand at 25℃ for 30min;

[0190] 4) 4C constant current charging to 0.03C0 Ah at 25℃;

[0191] 5) Stand at 25℃ for 8s;

[0192] 6) Repeat steps 4) and 5) at 25°C until the voltage in step 4) is ≥ 3.65V;

[0193] 7) Stand at 25℃ for 8s;

[0194] 8) Stand at 25℃ for 30min;

[0195] 9) 1C constant current discharge to 3.2V at 25℃; the discharge capacity is calculated as C1 Ah,

[0196] 10) Calculate the 4C rate charging window of the battery cell as C1 / C0, in %SOC.

[0197] The higher the 4C rate charging window, the better the rate performance of the battery cell.

[0198]

[0199] According to the results in Table 1, the charging window at 4C rate is significantly improved in each embodiment compared with the comparative example, indicating that the use of conductive fiber materials can effectively reduce the resistance of the pole piece, thereby reducing the internal resistance of the battery, reducing polarization during charging and discharging, and improving the battery rate performance. In comparative example 1-1, conventional carbon nanotubes are used as conductive agents in the positive pole piece, and conventional conductive carbon black is used as conductive agent in the negative pole piece. Compared with the conductive fiber materials in each embodiment, it is more difficult for the two to form a conductive network with good conductivity. Therefore, the resistance of the pole piece is large, and the DC impedance of the battery is high, that is, the internal resistance of the battery is large, and the rate performance of the battery is poor.

[0200] According to Examples 1-1 to 1-4, the aspect ratio of the conductive fiber material has a certain influence on the internal resistance of the battery. When the aspect ratio is 200 to 1500, the charging window at 4C rate is higher, and the rate performance of the battery is better, and it is further preferably 400 to 800.

[0201] According to Examples 1-1 to 1-9, when the average diameter of the conductive fiber material is 2 to 50 μm, the average diameter is 10 to 100 nm, and the thickness of the conductive layer is 3 to 20 nm, the charging window of the battery at 4C rate can be effectively broadened and the rate performance of the battery can be improved.

[0202] According to Examples 1-3, 1-10 to 1-12, the type of conductive layer in the conductive fiber material has a certain influence on the internal resistance of the battery. Compared with conductive metal oxides, conductive carbon and conductive polymers, metal as a conductive layer can further broaden the charging window of the battery at 4C rate and further improve the rate performance of the battery.

[0203] According to Examples 1-3, 1-13 and 1-14, the above three organic fibers have little effect on the internal resistance of the battery. This may be because the above three organic fibers have good flexibility, which can effectively broaden the charging window of the battery at 4C rate and improve the rate performance of the battery.

[0204] According to Examples 1-3 and 1-15, dispersing the conductive fiber material in advance and then preparing the positive electrode slurry can further broaden the charging window of the battery at 4C rate and improve the rate performance of the battery.

[0205] According to Examples 1-1 to 1-17, using conductive fiber materials in the positive electrode sheets instead of commonly used carbon nanotubes and conductive carbon black can effectively broaden the battery's charging window at 4C rate and improve the battery's rate performance.

[0206] Example 2-1 to Example 2-6

[0207] It is substantially the same as Example 1-3, except that the mass percentage of the conductive fiber material in the positive electrode sheet in the positive electrode film layer is different, the mass percentage of lithium iron phosphate in the positive electrode film layer is adjusted accordingly, and the binder content remains unchanged.

[0208] The lithium-ion batteries obtained in the above-mentioned Examples 2-1 to 2-6 were subjected to a 4C rate charging window test. The test results are shown in Table 2.

[0209] Table 2

[0210] Mass percentage of conductive fiber material in positive electrode film layer (%) 25℃4C rate charging window (%) Example 2-1 0.01 62 Example 2-2 0.05 71 Example 2-3 0.1 77 Examples 1-3 0.15 79 Embodiment 2-4 0.3 80 Embodiment 2-5 1 82 Embodiment 2-6 3 83

[0211] According to the results in Table 2, adding a small amount of conductive fiber material to the electrode plate can effectively broaden the battery charging window at 4C rate and improve the battery rate performance. Therefore, the use of this conductive fiber material can appropriately reduce its content in the positive electrode film layer, thereby improving the energy density of the battery. When the mass percentage of the conductive fiber material in the positive electrode film layer is 0.01% to 3%, the battery has a higher charging window at 4C rate and better rate performance.

[0212] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electrode plate, characterized in that: It comprises an electrode material film layer, wherein the electrode material film layer comprises a conductive fiber material, wherein the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a part of the surface of the organic fibers, wherein the conductive layer comprises a conductive material.

2. The electrode plate according to claim 1, characterized in that: The aspect ratio of the conductive fiber material is 200-1500.

3. The electrode plate according to claim 2, characterized in that: The aspect ratio of the conductive fiber material is 400-800.

4. The electrode sheet according to any one of claims 1 to 3, characterized in that: The conductive fiber material satisfies at least one of the following conditions: 1) The average diameter of the conductive fiber material is 10 to 100 nm; 2) The average length of the conductive fiber material is 2 to 50 μm.

5. The electrode plate according to claim 4, characterized in that: The conductive fiber material satisfies at least one of the following conditions: 1) The average diameter of the conductive fiber material is 20 to 60 nm; 2) The average length of the conductive fiber material is 10 to 30 μm.

6. The electrode plate according to claim 4, characterized in that: The thickness of the conductive layer is 3-20 nm.

7. The electrode plate according to claim 6, characterized in that: The thickness of the conductive layer is 5-10 nm.

8. The electrode plate according to claim 1, characterized in that: The organic fiber includes at least one of protein fiber, polysaccharide fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber or polyether fiber.

9. The electrode plate according to claim 1, characterized in that: The conductive material includes at least one of a metal element, an alloy, conductive carbon, a conductive metal oxide or a conductive polymer.

10. The electrode plate according to claim 9, characterized in that: The metal element comprises at least one of copper, nickel, aluminum, silver or titanium; and / or, the alloy comprises at least one of a copper alloy, a nickel alloy, an aluminum alloy, a silver alloy or a titanium alloy; and / or, the conductive carbon comprises at least one of carbon nanotubes, conductive carbon black or graphene; and / or, the conductive metal oxide comprises at least one of zinc oxide, indium tin oxide or tin oxide; And / or, the conductive polymer includes at least one of polypyrrole and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid).

11. The electrode plate according to claim 1, characterized in that: The mass percentage of the conductive fiber material in the electrode material film layer is 0.01% to 3%.

12. A method for preparing an electrode sheet, characterized in that: The following steps are involved: Dispersing a conductive fiber material, an active material and a binder in a solvent to obtain an electrode slurry, wherein the conductive fiber material comprises: organic fibers and a conductive layer coated on at least a portion of the surface of the organic fibers; The electrode slurry is dried to obtain an electrode material film layer.

13. The method according to claim 12, characterized in that The step of dispersing the conductive fiber material, the active material and the binder in a solvent to obtain the electrode slurry specifically comprises: Firstly, the conductive fiber material is dispersed in a solvent to obtain a conductive fiber material dispersion liquid, and then the conductive fiber material dispersion liquid, an active material and a binder are dispersed in the solvent to obtain an electrode slurry.

14. A battery, characterized in that: It comprises the electrode plate according to any one of claims 1 to 11 or the electrode plate prepared according to the method according to claim 12 or 13.

15. An electrical device, characterized in that: Comprising the battery of claim 14.

Citation Information

Cited By

  • Cement-based electrode, capacitor and preparation method thereof

    CN121237574A

  • Cement-based electrode, capacitor and method for manufacturing the same

    CN121237574B